Acid activated Serra de Dentro bentonite: chemical, structural, textural and catalytic properties - Fernandes, C. (2012)
A bentonite collected at Serra de Dentro, Porto Santo Island, Portugal was selected as the starting material for the preparation of acid activated clay catalysts. These materials were prepared using a range of different HCl concentrations, contact times and temperatures. The materials obtained were characterized in terms of chemical composition (XRF), structure (XRD and IR spectroscopy), textural properties (adsorption-desorption isotherms of N2 at 77K), acidity (TG of cyclohexylamine saturated samples) and catalytic activity (limonene conversion). Results show that increasing the harshness of the acid treatments produces more active catalysts, although this increased catalytic behaviour does not correlate directly with the calculated surface areas nor with the acidity values. A tentative explanation for this catalytic behaviour is given.